Perceived feasibility of an occupation-based telerehabilitation intervention for older adults with chronic health conditions in Israel - Aviva Beit Yosef; Talia Maeir; Fatena Khalailh; Yafit Gilboa (SAGE Publishing, 2022)
Aims Our study explored the perceived feasibility of using a home-based telerehabilitation service for older adults with chronic health conditions in Israel. Method This mixed-methods study included two focus groups of registered occupational therapists ( n = 10) working in rehabilitation wards in Israel. Participants completed an open-ended questionnaire and Likert scale items so that data could be gathered on their perspectives regarding using an in-home telerehabilitation service for older adults after discharge from rehabilitation units. Thematic analysis with an a priori coding approach was applied to the data. Results Perceived advantages included transfer to the natural environment and the overcoming of geographical distance. Caregiver support and patient motivation were recognized as enabling factors. Perceived barriers included lack of hands-on contact and the concern that safety could be impeded by technological challenges and the patients' cognitive status. Conclusions Findings from this study can potentially contribute to facilitating the implementation of a home-based telerehabilitation service as a practical alternative for elderly patients after discharge from rehabilitation units in Israel.